Taxonomic revision of the genus Gamochaeta Wedd. (Gnaphalieae, Asteraceae) in Chile - Freire, Susana Edith (2016)
Twenty four species of Gamochaeta (Gnaphalieae, Asteraceae), G. aliena, G. alpina, G. americana, G. andina, G. axillaris, G. chamissonis, G. depilata, G. deserticola, G. falcata, G. filaginea, G. humilis, G. longipedicellata, G. neuquensis, G. nivalis, G. oligantha, G. procumbens, G. ramosa, G. serpyllifolia, G. simplicicaulis, G. spiciformis, G. stachydifolia, G. subfalcata, G. valparadisea, and G. villarroelii, are formally monographed with morphological descriptions, illustrations, geographic distribution and habitat, distribution maps, phenology, lists of representative specimens examined, and a comprehensive identification key for every species. A new name Gamochaeta ramosa S.E. Freire, N. Bayón & C.M. Baeza for Gnaphalium ramosum Phil. (1864) non Lam. (1779) nec Sch. Bip. (1845), is proposed. The following taxa are newly synonymized: Gamochaeta foliosa with G. spiciformis; G. monticola with G. oligantha; Gnaphalium petraeum with Gamochaeta andina; G. suffruticosa with G. chamissonis; Gnaphalium bellidifolium, Gamochaeta berteroana with G. filaginea; and Gnaphalium agreste with Gamochaeta stachydifolia. Lectotypes are newly designated for Gnaphalium andinum, G. berteroanum, G. suffruticosum, and G. villarroelii.